Psilorhynchus tysoni, a new species of torrent minnow from the Salween River drainage, western Thailand (Teleostei: Psilorhynchidae) - Conway, Kevin W.; Pinion, Amanda K. (Zootaxa, 2016)
Psilorhynchus tysoni, new species, is described on the basis of 10 specimens, 23.3–53.8 mm SL from the Mae Nam Moei and Hue Mae Song Rivers, in the Salween River drainage in western Thailand. It belongs to the P. nudithoracicus species group and can be distinguished from other members of this group by a combination of characters, including features of body and fin coloration, head shape, and caudal fin-ray, vertebrae, and cephalic lateral-line canal pore counts. Phylogenetic analyses of a mitochondrial DNA data set (comprising 642 bp of cytochrome c oxidase subunit 1 and 1140 bp of cytochrome b) for 12 species of Psilorhynchus and one outgroup taxon resulted in phylogenetic hypotheses in which P. tysoni is a member of a clade equivalent to the P. nudithoracicus species group. Within this group P. tysoni is placed as the sister taxon of a putatively undescribed species of Psilorhynchus from Myanmar.